Pengaruh Iklan dan Public Relation terhadap Citra Institusi dan Keputusan Mahasiswa Memilih Kampus STIKI Malang sebagai Tempat Studi: Pengaruh Iklan dan Public Relation terhadap Citra Institusi dan Keputusan Mahasiswa Memilih Kampus STIKI Malang sebagai Tempat Studi (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2018)
Advertising and public relations is one of the student new admissions marketing strategy at campus STIKI Malang. Both strategies are used to be on target with increasingly changing technological changes and developments that are balanced by the increasing level of competition among educational institutions. Media marketing is expected to contribute to the institution's image and selection decisions for students. This study is intended to address the following issues: (1) How does advertising influence the institutional image? (2) What is the influence of public relations on the institution's image? (3) How does advertising influence student decisions in choosing where to study? (4) How is the influence of the PR on the decision of the student in choosing the place of further study? (5) How does the institution's image influence the student's decision in choosing the place of further study? The research method used is descriptive quantitative by using questionnaires and interview instruments. Respondents in this study are all students STIKI Malang force 2016 as many as 250 people in four courses namely Informatics Engineering, Information Systems, Information Management and Visual Communication Design.